PENGARUH PENGALAMAN MAGANG TERHADAP NIAT BERWIRAUSAHA MAHASISWA (STUDI PADA MAGANG MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI DI MINI MARKET TANIA FKIP UNS) - -, Ana Ernita Kusuma Arum -; -, Mintasih Indriayu - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2016)
This study describes internship experiences contribution as an antecedent on the relationship between Theory of Planned Behavior (TPB) and entrepreneurial intention. Internship experiences can be divided into five aspects: sensory experiences, affective experiences, physics experiences, cognitive-creative experiences and relation experiences. The purpose of this study is to examine the effect of the TPB and its impact on entrepreneurial intention. This research used descriptive quantitative method and the technique of data analysis used Structural Equation Model-Partial Least Square (SEM-PLS).The respodents of the research are fourth and fifth year students of economics education. This research showed that : (1) There were a positive and insignificant influence between sensory experiences and attitude toward behavior; there were a negative and insignificant influence between sensory experiences and subjective norm; there were a positive and insignificant influence between sensory experiences and perceived behavior control. (2) There were a positive and insignificant influence between affective experiences and attitude toward behavior; there were a positive and insignificant influence between affective sensory experiences and subjective norm; there were a negative and insignificant influence between affective experiences and perceived behavior control.(3) There were a negative and insignificant influence between physic experiences and attitude toward behavior; there were a positive and insignificant influence between physic experiences and subjective norm; there were a negative and insignificant influence between physic experiences and perceived behavior control. (4) There were a positive and significant influence between cognitive-creative experiences and attitude toward behavior; there were a positive and significant influence between cognitive-creative experiences and subjective norm; there were a positive and significant influence between cognitive-creative experiences and perceived behavior control. (5) There were a positive and insignificant influence between relational experiences and attitude toward behavior; there were a positive and insignificant influence between relation experiences and subjective norm; there were a positive and insignificant influence between relation experiences and perceived behavior control. (6) There were a positive and significant influence between attitude toward behavior, subjective norm and perceived behavior control to the entrepreneurial intention.